1996
DOI: 10.1128/jb.178.15.4555-4562.1996
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory control determines respiration and nitrogenase activity of Rhizobium leguminosarum bacteroids

Abstract: The relationship between the O 2 input rate into a suspension of Rhizobium leguminosarum bacteroids, the cellular ATP and ADP pools, and the whole-cell nitrogenase activity during L-malate oxidation has been studied. It was observed that inhibition of nitrogenase by excess O 2 coincided with an increase of the cellular ATP/ADP ratio. When under this condition the protonophore carbonyl cyanide m-chlorophenylhydrazone (CCCP) was added, the cellular ATP/ADP ratio was lowered while nitrogenase regained activity. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…Previous in vitro analyses showed that the PBS is an acidic compartment (Bhandari & Nicholas ; Udvardi & Day ; Fougere & Le Rudulier ; Haaker et al . ) and in vivo data described in this manuscript, using LysoTrackers DND‐99 and DND‐189, confirm and reinforce that the PBS compartment is acidic. However, it remains to be determined whether pH variations occur in the PBS throughout symbiosis.…”
Section: Resultssupporting
confidence: 81%
“…Previous in vitro analyses showed that the PBS is an acidic compartment (Bhandari & Nicholas ; Udvardi & Day ; Fougere & Le Rudulier ; Haaker et al . ) and in vivo data described in this manuscript, using LysoTrackers DND‐99 and DND‐189, confirm and reinforce that the PBS compartment is acidic. However, it remains to be determined whether pH variations occur in the PBS throughout symbiosis.…”
Section: Resultssupporting
confidence: 81%
“…Endophytic rhizobia acquire carbon from host plants in the form of C 4 -dicarboxylates (fumarate, malate, and succinate), which can easily penetrate peribacteroid membranes of root nodules (Mitsch et al, 2018). Specifically, L-malate (C 4 H 6 O 5 ) is the key C 4 -dicarboxylate that supplies carbon to symbiotic rhizobia in root nodules (Haaker et al, 1996;Poole and Allaway, 2000;Mitsch et al, 2018). Rhizobial TCA cycle functions aerobically in free-living cells (Maier, 2004), and microaerobically involving anaplerotic enzymatic pathways in endophytic bacteroids (Dunn, 1998).…”
Section: Carbon Acquisition By Endophytic Rhizobium Speciesmentioning
confidence: 99%
“…Cells were subsequently centrifuged and suspended in 3 ml of 25 mM TES [N-tris(hydroxymethyl)methyl)methyl-2-aminoethanesulfonic acid]-KOH-5 mM MgCl 2 buffer (pH 6.8) containing 10 g of RNase per ml, 10 g of DNase I per ml, and 1 mM phenylmethylsulfonyl fluoride. Membrane vesicles were prepared as described by Haaker et al (16).…”
Section: Isolation Of Membranes Bacterial Cultures Grown In An Oxystmentioning
confidence: 99%
“…The cytochrome cbb 3 cytochrome c oxidase, encoded by the fixNOQP operon in rhizobial species (18,23,32,38,50) or by a similar cco(cyt)NOQP operon in other bacteria (7,39,43,45), appears to be a cytochrome c terminal oxidase belonging to the heme-copper oxidase superfamily (14). In most rhizobial species this oxidase is essential for nitrogen-fixing endosymbiosis (18,32,50) and is characterized by an extremely high O 2 affinity (16,33). In the bacteria Magnetospirillum magnetoaceticum and Agrobacterium tumefaciens, and in Azorhizobium caulinodans growing nonsymbiotically, the cbb 3 -type cytochrome c terminal oxidase seems to be at least partially responsible for the microaerobic respiration (23,39,43).…”
mentioning
confidence: 99%